2011
DOI: 10.1037/a0024859
|View full text |Cite
|
Sign up to set email alerts
|

Content and discovery in the dreams of Canadian male university students: A pilot study.

Abstract: This study extended previous research by exploring Canadian male university students because only the dreams of females had been previously assessed. Dream content and discovery passages were scored using the Hall and Van de Castle (1966) content analysis guidelines. Discovery was assessed via The Storytelling Method of dream interpretation. Thirty-nine male students provided one dream each. Content categories, discovery categories, and content and discovery categories together were analyzed for significant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Threat in the dreams of soldiers was associated with combat scenes, success, and failures, and dream imagery of the enemy was associated with success in dream imagery. Dale et al (2012) also found that when compared to civilian males, male soldiers' dreams contained more weapons, aggression, death, threat, and combat scenes. Research on what soldiers learn about waking day life from dream imagery through dream interpretation has yet to be examined.…”
Section: Dreams Of Soldiersmentioning
confidence: 86%
See 3 more Smart Citations
“…Threat in the dreams of soldiers was associated with combat scenes, success, and failures, and dream imagery of the enemy was associated with success in dream imagery. Dale et al (2012) also found that when compared to civilian males, male soldiers' dreams contained more weapons, aggression, death, threat, and combat scenes. Research on what soldiers learn about waking day life from dream imagery through dream interpretation has yet to be examined.…”
Section: Dreams Of Soldiersmentioning
confidence: 86%
“…Furthermore, predictions of dream discovery were made from dream content. The use of content analysis on discovery passages as well as the predictive value of dreams has also been demonstrated and found to be effective with Canadian male (Dale & DeCicco, 2012) and female (DeCicco, 2007a) university students. DeCicco and Higgins (2009) also used content analysis for discovery categories when comparing the dreams of alcoholics to non-alcoholics and each group gained discovery that was relevant to their waking day circumstances.…”
Section: Discovery and Content Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28] The Threat Simulation Theory states that there will be an increase in dreams with threat imagery that accompanies experiencing life-threatening situations, and this can be used as a survival technique. [29][30][31] With video games, it has been shown that virtual life-threatening situations do not elicit violent and aggressive dreams, 27 since there is frequent rehearsal of life-threatening situations with no real presence of danger.…”
Section: Gaming and Dreamsmentioning
confidence: 99%